2015
DOI: 10.1017/aae.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Potential Standing Timber Insurance

Abstract: Landowners rarely insure standing timber, suggesting the limited products available do not appeal to potential clientele. We estimated landowner willingness to pay (WTP) for standing timber insurance. Data were generated through a contingent valuation survey. Questionnaires were mailed to a random sample of Mississippi private forest landowners with 100+ acres of forestland. WTP for standing timber insurance was derived using an interval-censored survival model and a Kaplan-Meier Turnbull nonparametric model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
3
21
2
1
Order By: Relevance
“…Risk perceptions and mitigation behaviors reflect a complex web of contextual influences, with economic tradeoffs potentially acting as a fairly limited aspect of decision-making [24] [28] [29]. The risk may not be salient in the antecedent conditions of residents who, while understanding that a catastrophic event is likely, may do little to mitigate the potential consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk perceptions and mitigation behaviors reflect a complex web of contextual influences, with economic tradeoffs potentially acting as a fairly limited aspect of decision-making [24] [28] [29]. The risk may not be salient in the antecedent conditions of residents who, while understanding that a catastrophic event is likely, may do little to mitigate the potential consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This work would examine storage and reloading of recovered material, as well as spatial distribution of forest products manufacturers relative to raw material supply. Third, research is needed regarding landowners' motivations for purchasing timber insurance as well as innovative insurance tools that appeal to customers [24]. An Internet information portal could provide insurance information to stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar forest insurance study, Sauter et al (2016) considered risk aversion, education and forest experience as controls to insure or not to insure forest stands. Further, Deng et al (2015) examined the willingness to pay (WTP) for timber insurance. Risk perception, risk aversion and years of land ownership positively affected the WTP for timber insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning forest fire insurance, Brunette et al (2015b) reported that only 1.25% of the insurable land in Spain is insured, and less than 0.5% of the forest cover in Slovakia. Such insurance also exists outside of Europe, in New Zealand (Manley and Watt 2009), China (Dai et al 2016), and USA (Deng et al 2015), for example.…”
Section: Introductionmentioning
confidence: 99%